O lugar da Matemática na educação infantil: um estudo sobre as atitudes e crenças de autoeficácia das professoras no trabalho com as crianças - Tortora, Evandro [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This research aimed to answer the following research question: "What are the possible relationships between beliefs of self-efficacy at work with mathematical knowledge, attitudes towards mathematics and the teaching practice in early childhood education?". This study was developed in the light of psychology assumptions, such as Bandura's Social Cognitive Theory (1986, 1989, 2008) and research on Brito's Attitudes (1996), and researchers in Mathematics Education, such as Lorenzato (2008). This study included 115 teachers of early childhood education. The instruments used in this study were: 1) a self-efficacy scale on working with mathematics in early childhood education, built and validated for this study; 2) a scale of attitudes toward mathematics for preschool teachers adapted for this study; 3) a questionnaire; 4) a semi-structured interview; 5) a field diary for systematic observation of teachers' practices with children. In total, 115 teachers answered both scales, of which 55 answered the questionnaire. Among this group, two teachers gave the interview and authorized the researcher to participate in their activities with the children. The analysis of the data showed that: 1) Most teachers have positive self-efficacy beliefs about working with mathematics, whose main source is direct experience and vicarious experience. Vicarious experience and social persuasion are considered most influential in forming positive self-efficacy beliefs; 2) Most teachers have attitudes that tend to be positive about math; 3) there is a moderate, positive and significant correlation between self-efficacy beliefs in working with mathematics in early childhood education and attitudes toward mathematics; 4) Positive experiences in relation to mathematics seem to have more strength in the formation of teachers' self-efficacy attitudes and beliefs, as they seek to overcome negative practices experienced by them as students; 5) The teachers declared a selfefficacy in problem solving work, however, a qualitative analysis of the questionnaires and interviews showed that the idea of "problem" for the teachers is linked to everyday situations or questions to be answered. The “challenging” character of the problem was considered by approximately half of the teachers; 6) Interviews show that teachers have self-efficacy beliefs and positive attitudes and this reflects how they plan children's interactions with mathematical knowledge; 7-) Observations of teachers 'practices illustrate the problematic posture that mathematics can be worked on in early childhood education. In addition, teachers' positive attitudes and beliefs show an openness to dialogue about their practice and constant concern for learning new forms of interaction. with math in kindergarten. However, both teachers lack training to enable experiences that involve greater autonomy of children in exploring the times, spaces and resources used to develop mental processes necessary for learning mathematical concepts.

Esta pesquisa se propôs a responder a seguinte questão: “Quais são as possíveis relações entre as crenças de autoeficácia no trabalho com conhecimentos matemáticos, as atitudes em relação à matemática e a prática docente de professoras e professores da Educação Infantil?”. Este estudo foi desenvolvido à luz de pressupostos da Teoria Social Cognitiva de Bandura (1986, 1989, 2008), das pesquisas sobre Atitudes de Brito (1996) e de estudos relacionadas à Educação Matemática, como o trabalho de Lorenzato (2008). Participaram desta pesquisa 115 professoras da Educação Infantil. Os instrumentos utilizados foram: 1) uma escala de autoeficácia sobre o trabalho com matemática na Educação Infantil, construída e validada para este estudo; 2) uma escala de atitudes em relação à matemática para professores de Educação Infantil adaptada para este estudo; 3) um questionário; 4) uma entrevista semiestruturada; 5) um diário de campo para observação sistemática das práticas das professoras com as crianças. No total, 115 professoras responderam a ambas as escalas, das quais 55 responderam ao questionário. Dentre esse grupo, duas professoras concederam a entrevista e autorizaram que o pesquisador participasse das suas atividades com as crianças. A análise dos dados mostrou que: 1) As professoras, em sua maioria, apresentam crenças de autoeficácia positivas com relação ao trabalho com matemática, as quais tem como fonte principal a experiência direta e a experiência vicária. A experiência vicária e a persuasão social são consideradas mais influentes na formação de crenças de autoeficácia positivas; 2) A maioria das professoras apresenta atitudes que tendem a ser positivas em relação à matemática; 3) existe uma correlação moderada, positiva e significativa entre as crenças de autoeficácia no trabalho com matemática na Educação Infantil e as atitudes em relação a matemática; 4) As experiências positivas em relação à matemática parecem ter mais força na formação de atitudes e crenças de autoeficácia das professoras, uma vez que estas buscam superar práticas negativas vivenciadas por elas enquanto alunas; 5) As professoras declararam uma autoeficácia no trabalho com resolução de problemas, porém, uma análise qualitativa dos questionários e das entrevistas mostrou que a ideia de “problema”, para as professoras, está ligada a situações do cotidiano ou questões a serem respondidas. O caráter “desafiador” do problema foi considerado por aproximadamente metade das professoras; 6) As entrevistas mostram que as professoras têm crenças de autoeficácia e atitudes positivas e que isso reflete na forma como elas planejam as interações das crianças com conhecimentos matemáticos; 7-) As observações das práticas das professoras, ilustram a postura problematizadora que a matemática pode ser trabalhada na Educação Infantil, além disso as atitudes e crenças positivas das professoras demostram uma abertura ao diálogo sobre sua prática e constante inquietação por aprender novas formas de interação com a matemática na Educação Infantil. Porém, ambas as professoras carecem de formação para possibilitar vivências que envolvam maior autonomia das crianças na exploração dos tempos, espaços e recursos usados para o desenvolvimento de processos mentais necessários para a aprendizagem de conceitos matemáticos
The place of Mathematics in early childhood education: a study on teachers' attitudes and self-efficacy beliefs when working with children
Keywords: Mathematics; Early childhood education; Childhood; Self-efficacy.; Attitudes; Matemática; Educação Infantil; Infância; Autoeficácia; Atitudes